Preparation of a pH‐responsive chitosan‐montmorillonite‐nitrogen‐doped carbon quantum dots nanocarrier for attenuating doxorubicin limitations in cancer therapy. Issue 10 (13th September 2022) - Rahmani, Erfan; Pourmadadi, Mehrab; Ghorbanian, Sohrab Ali; Yazdian, Fatemeh; Rashedi, Hamid; Navaee, Mona
Abstract: Despite its widespread usage as a chemotherapy drug in cancer treatment, doxorubicin (DOX) has limitations such as short in vivo circulation time, low solubility, and poor permeability. In this regard, a pH‐responsive chitosan (CS)‐ montmorillonite (MMT)‐ nitrogen‐doped carbon quantum dots (NCQDs) nanocomposite was first developed, loaded with DOX, and then incorporated into a double emulsion to further develop the sustained release. The incorporated NCQDs into the CS‐MMT hydrogel exhibited enhanced loading and entrapment efficiencies. The presence of NCQDs nanoparticles in the CS‐MMT hydrogel also resulted in an extended pH‐responsive release of DOX over a period of 96 h compared to that of CS‐MMT‐DOX nanocarriers at pH 5.4. Based on the Korsmeyer‐Peppas model, there was a controlled DOX release at pH 5.4, while no diffusion was observed at pH 7.4, indicating fewer side effects. MTT assay showed that the cytotoxicity of DOX‐loaded CS‐MMT‐NCQDs hydrogel nanocomposite was significantly higher than those of free DOX ( p < 0.001) and CS‐MMT‐NCQDs ( p < 0.001) on MCF‐7 cells. Flow cytometry results demonstrated that a higher apoptosis induction achieved after incorporating NCQDs nanoparticles into CS‐MMT‐DOX nanocarrier. These findings suggest that the DOX‐loaded nanocomposite is a promising candidate for the targeted treatment of cancer cells.